The effect of foot reflexology massage on pruritus in hemodialysis patients - Azar Shahriari; Hamed Sarani; Sara Sheikh; Azizollah Arbabisarjou (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Pruritus is a common skin manifestation in patients undergoing hemodialysis. Pruritus has a negative impact on the quality of life of patients receiving hemodialysis. This study was aimed to investigate the effect of foot reflexology massage on pruritus in hemodialysis patients. MATERIALS AND METHODS: A quasi-experimental study was conducted on 90 hemodialysis patients referred to Khatam-al-Anbiya and Ali-Ebne Abi-Taleb hospitals affiliated to Zahedan University of Medical Sciences in 2019. Patients with moderate-to-severe pruritus scores obtained from the Pruritus Severity Scale (PSS) were included in the study. They were randomly divided into intervention and control groups using shuffling cards or envelopes. The intervention group received nine sessions of foot reflexology massage 3 days a week for 20 min (10 min on each foot) with an emphasis on the solar plexus point. The participants in both groups again completed the PSS 48 h after the intervention. Data were analyzed using the SPSS version 24, independent t-test, Chi-square test, and paired t-test. RESULTS: The results of this study demonstrated that foot reflexology massage significantly reduced itching or pruritus in hemodialysis patients (P < 0.001). Pruritus scores in the control group were statistically significant (P < 0.001). There was no significant statistically difference between the two groups in terms of the pruritus scores before the intervention (P = 0.59). CONCLUSION: Our findings showed that the foot reflexology massage could relieve itching or pruritus in hemodialysis patients. It is, therefore, recommended that it can be used as an effective intervention technique to alleviate itching in hemodialysis patients.